2016
DOI: 10.1016/j.ijfoodmicro.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Use of Schizosaccharomyces strains for wine fermentation—Effect on the wine composition and food safety

Abstract: a b s t r a c tSchizosaccharomyces was initially considered as a spoilage yeast because of the production of undesirable metabolites such as acetic acid, hydrogen sulfide, or acetaldehyde, but it currently seems to be of great value in enology.o ced Nevertheless, Schizosaccharomyces can reduce all of the malic acid in must, leading to malolactic fermentation. Malolactic fermentation is a highly complicated process in enology and leads to a higher concentration of biogenic amines, so the use of Schizosaccharomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 62 publications
5
72
1
Order By: Relevance
“…In this respect, S. pombe perform effective malic acid deacidification and significantly reduces the levels of biogenic amines and ethyl carbamate precursors without the need for any secondary bacterial MLF (Benito et al, 2014, 2016b). Mylona et al (2016) confirmed the ability of yeast to produce safe wines.…”
Section: Non-saccharomyces Yeastsmentioning
confidence: 58%
See 2 more Smart Citations
“…In this respect, S. pombe perform effective malic acid deacidification and significantly reduces the levels of biogenic amines and ethyl carbamate precursors without the need for any secondary bacterial MLF (Benito et al, 2014, 2016b). Mylona et al (2016) confirmed the ability of yeast to produce safe wines.…”
Section: Non-saccharomyces Yeastsmentioning
confidence: 58%
“…The world wine market is experiencing increasing interest in new yeast strains that can produce unique wines with novel properties (Mylona et al, 2016). Non- Saccharomyces yeasts have garnered interest in winemaking due to their beneficial effects and because consumers are demanding new wine styles (Lleixà et al, 2016).…”
Section: Non-saccharomyces Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar must pasteurizations carried out by other authors reduced microbial must contamination by four logarithmic units, but were not able to sterilize it (Mylona et al . ). What this situation demonstrated was that these yeasts were not able to develop in grape must and that under industrial conditions, yeast coming from the must would overtake them.…”
Section: Resultsmentioning
confidence: 97%
“…This fact oblige winemakers to control these undesirable compounds form a winemaking point of view. The main parameters to control are ochratoxin A, biogenic amines [9], ethyl carbamate, sulfur dioxide, allergens, pesticides, genetically modified organisms, physical hazards and phthalates [4].…”
mentioning
confidence: 99%